Temporal and spatial distribution of dissolved oxygen in the Ria de Aveiro lagoon - Lopes, J. F.
Ria de Aveiro is a very important area of the Portuguese coast, which has been under an increasing anthropogenic pressure, for several decades, contributing to the degradation of the lagoon’s water quality. A water quality model was applied to predict concentrations of inorganic nutrients, chlorophyll-a, and dissolved oxygen (DO) in the Ria de Aveiro lagoon, Portugal. Both data and modelling results point out that the DO distribution in the lagoon is controlled by tidal transport processes. The DO distribution in the Ria de Aveiro seems to bemainly controlled by tidal processes, as its concentration remains relatively high and close to sea values. The far end of the lagoon, where the intertidal salt marshes are important, the DO concentration is dominantly affected by re-aeration and the flooding/drying processes over the intertidal salt marshes, the phytoplankton activity, the nitrification processes and oxidation of the organic matter. These processes play an important role in the creation of the summer hypoxic/anoxic situations, when primary production and advective transport are low. Data and modelling results show strong relationship between nutrients and the CHL-a concentrations during spring–summer, but weak during winter–spring, evidencing the light and nutrients limiting effect during, respectively the last and the former period. High NO3 and NH4 concentrations or important spikes in the concentration precede or coincide, in general, with the CHL-a increase. The main results concerning the DO evolution and distribution demonstrate that a generalized eutrophication state is unlikely to occur within the lagoon, except near its very far end, during summer and in a situation of high BOD concentrations. The good connection between Ria de Aveiro lagoon and the sea and the circulation pattern inside the lagoon are, therefore, responsible for relatively high level of oxygen water content in the water column, throughout its main channels.